Gender, ethnicity and household labour in married and cohabiting couples in the UK - Man Yee Kan; Heather Laurie (University of Essex, Institute for Social and Economic Research (ISER), 2016)
There is an extensive literature on the domestic division of labour within married and cohabiting couples and its relationship to gender equality within and outside the household. UK quantitative research on the domestic division of labour across ethnic groups has been limited by a lack of data that enables disaggregation by ethnic group. This paper uses data from Understanding Society, the UK Household Longitudinal Study containing sufficient sample sizes of ethnic minority groups for meaningful comparisons. We find significant variations in patterns of domestic labour by ethnic group, gender, education and employment status after accounting for individual and household characteristics.
Keywords: D13; 330; domestic division of labour; ethnicity; gender